2000
DOI: 10.1007/s004380051197
|View full text |Cite
|
Sign up to set email alerts
|

The yeast peptidyl proline isomerases FPR3 and FPR4, in high copy numbers, suppress defects resulting from the absence of the E3 ubiquitin ligase TOM1

Abstract: Tom1p is a 3268-amino acid protein with extensive homology to the hect-domain class of E3 ubiquitin ligases. Disruption of the TOMI gene results in temperature sensitivity for growth. Genes encoding the peptidyl proline isomerases Fpr3p and Fpr4p, when present on multicopy plasmids, will suppress this temperature-sensitive growth phenotype. FPR3 can also suppress the mating defect seen in tom1 strains. Suppression is specific for disruption of TOM1, since FPR3 does not restore wild-type growth to strains lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The remaining two distinct nuclear FKBPs are both found in S. cerevisiae (Table 4B). ScFpr3 has been identified as nuclear (Benton et al , 1994; Manning‐Krieg et al , 1994; Shan et al , 1994), as has ScFpr4 (Davey et al , 2000; Dolinski et al , 1997b), with both ScFpr3 and ScFpr4 having been shown to suppress defects seen in the absence of the E3 ubiquitin ligase TOM1 (Davey et al , 2000). SpFKBP39a and CeFkb8 are the only distinct PSORT‐predicted cytoplasmic non‐human FKBPs (Table 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two distinct nuclear FKBPs are both found in S. cerevisiae (Table 4B). ScFpr3 has been identified as nuclear (Benton et al , 1994; Manning‐Krieg et al , 1994; Shan et al , 1994), as has ScFpr4 (Davey et al , 2000; Dolinski et al , 1997b), with both ScFpr3 and ScFpr4 having been shown to suppress defects seen in the absence of the E3 ubiquitin ligase TOM1 (Davey et al , 2000). SpFKBP39a and CeFkb8 are the only distinct PSORT‐predicted cytoplasmic non‐human FKBPs (Table 4B).…”
Section: Resultsmentioning
confidence: 99%
“…High-copy FPR3 or FPR4 also suppress ubiquitin ligase tom1 mutations [58]. Tom1 promotes destruction of Dia2, Cdc6 and other proteins [59], [60] and high-copy FPR3 might promote destruction of Tom1 targets similar to Glc7.…”
Section: Discussionmentioning
confidence: 99%
“…We do not believe that fpr3D acts in mitotic cells to suppress the mitotic DNA-damage checkpoint, because a checkpoint-defective mutation such as rad9D (which is by itself CPT sensitive) does not suppress the CPT sensitivity of rad52-D327. Another possibility is that a prolyl isomerase such as Fpr3 acts in the degradation of mutant proteins (Davey et al 2000). Perhaps Rad52-D327, a truncated protein-or another protein that depends on Rad52 interaction for its stability-is more stable in the absence of Fpr3.…”
Section: Discussionmentioning
confidence: 99%
“…This protein belongs to a very large family of related prolyl isomerases in budding yeast, and their absence has very minor effects on cell viability (Benton et al 1994;Davey et al 2000; http:// db.yeastgenome.org). It is possible that Fpr3 might act to improve the function of Rad51 protein in the absence of its interaction with the C terminus of Rad52.…”
Section: Discussionmentioning
confidence: 99%